Dendrocalamus strictus ((Roxb.) Nees): A Suitable Host for the Maintenance and Propagation of AM Fungi under Temperate Conditions. (9th April 2012) - Singh, Shipra; Kumar, Ajay; Pandey, Anita; Palni, Lok Man S.
Abstract : Dendrocalamus strictus ((Roxb.) Nees) was tested as a perennial host plant for propagation of an arbuscular mycorrhizal (AM) fungal consortium, initially isolated from rhizosphere of tea plants growing in the colder regions. The host performance in terms of colonization and spore production was compared with two annual hosts. The mycorrhizal dependency and growth enhancement potential were analyzed to test the suitability of D. strictus as a host plant. After 90 days of growth, 77.2% roots of D. strictus were found to be colonized by AM fungi with a spore count of 7 per g soil. AM fungal colonization and spore density values were lower in case of the host plants tested. Growth of D. strictus plants was found to be enhanced, in terms of all studied parameters; significant increases were recorded in shoot length as well as fresh and dry weight of shoots, a part of commercial importance. Similarly, P content, protein concentration, chlorophyll a and chlorophyll b contents were found to increase significantly. These data suggest that D. strictus can be used for the multiplication of AM fungi, isolated originally from the rhizosphere of tea; simultaneously, higher shoot biomass can provide additional economic benefit, using this environment friendly technology.